Seçilmiş OECD Ülkelerinin Ruh Sağlığı Hizmetleri Performansının Değerlendirilmesi - Çakmak, Cuma; Konca, Murat (Muş Alparslan Üniversitesi, 2019)
Mental health diseases are increasing all over the world. Mental healthservices’ impacts on welfare and health of the individual in addition toeconomic and social systems make them important. Despite this importance, mental health services are among the areas with low policy priority in healthsystems. The increase in social and economic losses caused by mental illnessbrings the effectiveness of mental health services to the agenda. The aim ofthis study is to assess the performance of mental health services of selectedOECD countries and to make comparisons among them. In this context, input-oriented Data Envelopment Analysis (DEA) with both Constant Return toScale (CRS) Model and Variable Return to Scale (VRS) Model has been utilized.In the study; number of psychiatric patient beds, number of psychiatry, numberof psychiatric nurses and number of psychologists were used as input variablesand as the output variable, the crude suicide rate was used. According to theCRS Model, three countries and according to the VRS Model, four countries werefound efficient. It is suggested that countries should take measures to reducethe rate of suicide by improving mental health services.

Ruh sağlığı hastalıkları tüm dünyada giderek artmaktadır. Gerekbireylerin refahı ve sağlığı gerekse ekonomik ve sosyal sistemler üzerine olanetkisi, ruh sağlığı hizmetlerini önemli kılmaktadır. Bu önemine rağmen, ruhsağlığı hizmetleri sağlık sistemleri içerisinde politika önceliği bakımındangerilerde görülmektedir. Ruhsal hastalıkların sebep olduğu sosyal ve ekonomikkayıpların artması, ruh sağlığı hizmetlerinin etkinliğini gündemegetirmektedir. Bu çalışmanın amacı, seçilmiş OECD ülkelerinin ruh sağlığıhizmetleri performansının değerlendirilmesi ve söz konusu ülkeler arasında karşılaştırmayapmaktadır. Bu kapsamda girdi yönelimli veri zarflama analizinin (VZA) ölçeğegöre sabit (CRS) ve değişken getirili (VRS) modellerinden faydalanılmıştır.Girdi değişkenleri olarak; psikiyatri hasta yatağı sayısı, psikiyatri sayısı, psikiyatri hemşiresi sayısı ve psikolog sayısı; çıktı değişkeni olarak ise, kaba intihar hızı kullanılmıştır. CRS Modeline göre üç, VRS Modeline göre dörtülke etkin bulunmuştur. Ülkelerin ruh sağlığı hizmetlerini geliştirerek kabaintihar hızlarını düşürecek önlemler almaları önerilmektedir.
Evaluation of Mental Health Services Efficiency of Selected OECD Countries
anemon
Keywords: Mental Health Services; Efficiency; Data Envelopment Analysis (DEA); Ruh Sağlığı Hizmetleri; Veri Zarflama Analizi (VZA); Etkinlik